EVALUATION OF SCREENING METHODS FOR BEHAVIORAL AND MUSCLE COORDINATION ACTIVITY OF ETHANOLIC EXTRACT OF CHAMAEMELUM NOBILE FLOWERS IN MICE - THAKUR, TAMANNA; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2025)
Objective: To evaluate muscle relaxants Activity of ethanolic extract of Chamaemelum in albino mice by using Open field test, Locomotion activity test, Rota Rod Method, and Inclined Plane Model. Methods: A total of 24 Swiss albino mice aged 6–8 w of either sex, weighing about 20-35g and maintained under standard laboratory conditions with controlled temperature (25±2 ˚C), humidity (40±10 %), and 12 h light and dark cycles each. Various CNS models using mice were used to evaluate behavioral and muscular coordination. Diazepam was a standard drug used for behavioral and muscular coordination activities. The ethanolic extract of Chamaemelum Nobile flowers with low and high doses (250 and 500 mg/kg) was administered orally in Swiss mice for 14 d and assessed Open field test, Locomotion activity test, Rota Rod Method, and Inclined Plane Model (IPM). The effects of diazepam (DZP; 4 mg/kg) through the i. p route were also assessed. The biochemical estimations after the 14th day evaluated plasma corticosterone levels. Result: In the present study, Chamaemelum Nobile (250 mg/kg and 500 mg/kg) Ethanolic extract was evaluated in albino Swiss mice in Open field test, Locomotion Activity Test, Rota Rod Method, and Inclined Plane Model. The effects of diazepam (DZP; 4 mg/kg) were also being assessed. Conclusion: In conclusion, study show that the ethanolic extract of Chamaemelum Nobile flowers is effective in inducing significant protection against behavioral and muscle coordination, as demonstrated by various CNS models for control.